Analysis of the knowledge of students of a private college in the interior of Bahia about the correct disposal of medicines (Research, Society and Development, 2021)
Disposal of medications has been discussed in recent years, the damage caused to the environment is the main concern. This study aimed to analyze the level of knowledge of pharmacy students at a private college in the interior of Bahia, regarding the disposal of expired or unused medications in their homes. It was a cross-sectional study, which adopted a descriptive study, being a qualitative and quantitative research. To understand how the interviewees dispose of expired or unused medications, an online questionnaire was applied, containing questions with the aim of identifying how medications are discarded and also knowing the degree of understanding of the risks involved in this practice brings. 56 students were interviewed, 69.8% women and 30.4% men. Of these respondents, 91.1% have medicines stored at home. 55.4% of respondents kept these drugs to be used again and only 1.8% took them to be discarded in pharmacies. When asked if they were aware of the matter, 76.8% said yes, but when faced with how they were discarded, 44.6% discarded it in household garbage, 23.2% never discarded it, 12.5% ​​discarded it in the toilet, 5.4% at the sink, 5.3% deliver to the pharmacy. It is clear that more in-depth studies related to the topic are needed. So that students have mastery over the subject, and when professionals can correctly guide their patients regarding the importance of correct disposal of medications.